A Rare Case of Vasculitis Patched Necrosis of Cecum due to Behçet’s Disease - Ehsan Shahverdi; Mehdi Morshedi; Faraneh Oraei-Abbasian; Maryam Allahverdi Khani; Roya Khodayarnejad (Case Reports in Surgery)
Isolated cecal necrosis is a rare form of acute ischemic colitis and a rare cause of surgical abdomen. Behçet’s disease is a multisystemic autoimmune condition which can induce vasculitis. This can result in cecal necrosis while disease involves colon vessels. We describe a patient with complicated Behçet’s disease and ischemic colitis admitted to our hospital. Patient was a 62-year-old female with more accompanying diseases. Histopathologic findings confirmed the diagnosis of ischemic colitis and regarding patient’s vision problem and skin lesions, rheumatologic tests were performed which were positive for HLAB5 and HLAB51 suggestive of Behçet’s disease; the patient was improved with surgery. Abdominal pain can indicate a disease with vascular involvement like Behçet’s disease, especially in the presence of other clinical findings suggestive of the disease including blurred vision and skin lesions. An abdominal computerized tomography (CT) scan is very diagnostic in the same patients.